2018
DOI: 10.1111/cge.13144
|View full text |Cite
|
Sign up to set email alerts
|

Detection of copy number variations in epilepsy using exome data

Abstract: Epilepsies are common neurological disorders and genetic factors contribute to their pathogenesis. Copy number variations (CNVs) are increasingly recognized as an important etiology of many human diseases including epilepsy. Whole-exome sequencing (WES) is becoming a standard tool for detecting pathogenic mutations and has recently been applied to detecting CNVs. Here, we analyzed 294 families with epilepsy using WES, and focused on 168 families with no causative single nucleotide variants in known epilepsy-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 45 publications
2
29
1
Order By: Relevance
“…For example, approximately 8% of reported results from GeneDx exomes (over 100,000 exome have been run in total, including currently >1,500 cases/month) are CNVs. Studies of cohorts affected by other conditions have identified significant rates of causative CNVs by next‐generation sequencing (NGS; Bergant et al, ; Overwater et al, ; Tsuchida et al, ). The detection of other structural variants as well as mosaicism by NGS, including from exome, genome, and targeted panels, is also improving (Stosser et al, ).…”
Section: Further Causes and Future Investigationsmentioning
confidence: 99%
“…For example, approximately 8% of reported results from GeneDx exomes (over 100,000 exome have been run in total, including currently >1,500 cases/month) are CNVs. Studies of cohorts affected by other conditions have identified significant rates of causative CNVs by next‐generation sequencing (NGS; Bergant et al, ; Overwater et al, ; Tsuchida et al, ). The detection of other structural variants as well as mosaicism by NGS, including from exome, genome, and targeted panels, is also improving (Stosser et al, ).…”
Section: Further Causes and Future Investigationsmentioning
confidence: 99%
“…Its efficiency at identifying single-nucleotide variants (SNVs) and small indels has been proven countless times. It also has recently been used for detecting CNVs, 16,17 but its performance and limitations for detecting CNVs are still undefined. We reanalyzed the WES data from our previously described cohort of 78 sequenced individuals 6 by focusing on CNV detection using ExomeDepth software 18 and identified a homozygous 8.4 kb intragenic deletion encompassing WDR66 (also known as CFAP251 [cilia-and flagella-associated protein 251 (MIM: 612573)]) exons 20 and 21 (out of 22) in seven individuals.…”
Section: Introductionmentioning
confidence: 99%
“…A retrospective, single-center cohort study evidenced that clinical signs, MRI, and targeted metabolic tests lead to an etiological diagnosis in about 13% of patients with “epileptic encephalopathy” [4]. In patients with a clinically unrecognized etiology (likely) causative de novo copy number variants (CNVs) accounted for about 3–10% of patients in several studies [48]. A large whole-exome sequencing study in “epileptic encephalopathy” patients established de novo variants, as disease cause in 12% [9].…”
Section: Introductionmentioning
confidence: 99%